REINFORCEMENT SISTEM PENDIDIKAN ISLAM PONDOK PESANTREN NURUL UMMAH BANTUL KOTAGEDE YOGYAKARTA - Robingun Suyud El Syam; hidayatu munawaroh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
This study seeks to reveal how the reinforcement of the Islamic education system at the Nurul Ummah Islamic Boarding School uses a type of qualitative field research. Primary data sources took direct interviews and then analyzed with support from secondary sources as explanatory. Research results: reinforcement of the Islamic education system at the Nurul Ummah Islamic Boarding School is an activity of the pesantren itself where the presentation of the curriculum used in Islamic boarding schools, especially in madrasah diniyah, is an integrated curriculum which contains character values. This means that between one subject matter and another has a direct link in the deepening of the subject matter. Evaluation of character education carried out by Islamic boarding schools is continuous, namely holding two semesters every year. The form of evaluation carried out emphasizes written exams in the form of multiple choice and essays as well as oral exams to test their abilities, the results achieved are quite good, this can be seen from the final score in the report card.